2009
DOI: 10.1186/1471-2334-9-193
|View full text |Cite
|
Sign up to set email alerts
|

Ertapenem versus piperacillin/tazobactam for the treatment of complicated infections: a meta-analysis of randomized controlled trials

Abstract: BackgroundErtapenem, a new carbapenem with a favorable pharmacokinetic profile, has been approved for the treatment of complicated intra-abdominal Infections (cIAIs), acute pelvic infections (APIs) and complicated skin and skin-structure infections (cSSSIs). The aim of this study is to compare the efficacy and safety of ertapenem with piperacillin/tazobactam, which has been reported to possess good efficacy for the treatment of these complicated infections.MethodsWe performed a meta-analysis of randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…[8][9][10][11][12][13][14][15] However, only three reviews included RCTs, and none assessed the certainty of evidence. 14,15,20 Of these, only one had a patient-important primary outcome and assessed risk of bias, but only regarding random sequence generation, allocation concealment and blinding. 15 In contrary to our assessment, authors concluded that the results were not affected by risk of bias.…”
Section: Relation To Current Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10][11][12][13][14][15] However, only three reviews included RCTs, and none assessed the certainty of evidence. 14,15,20 Of these, only one had a patient-important primary outcome and assessed risk of bias, but only regarding random sequence generation, allocation concealment and blinding. 15 In contrary to our assessment, authors concluded that the results were not affected by risk of bias.…”
Section: Relation To Current Evidencementioning
confidence: 99%
“…However, the mortality difference was less pronounced after excluding isolates non‐susceptible to piperacillin/tazobactam 7 . Previous systematic reviews comparing empirical or definitive treatment with β‐lactam/β‐lactamase inhibitors and carbapenems have demonstrated similar effects on mortality suggesting that piperacillin/tazobactam and other β‐lactam/β‐lactamase inhibitors may be safe alternatives to carbapenems 8–15 …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Diversos ensayos clínicos han demostrado la no inferioridad de ertapenem en el resultado clínico y microbiológico en la terapia de las patologías en las que está indicado e incluso, han mostrado superioridad frente a los manejos tradicionales como ampicilina-sulbactam, ceftriazona y piperacilina-tazobactam en pacientes con infecciones intraabdominales y del tracto genitourinario [12][13][14][15][16][17][18]. Esta superioridad se ex-presa en términos del porcentaje de pacientes tratados exitosamente, respuesta microbiológica favorable, curación, el perfil de seguridad, la costoefectividad y la menor inducción de resistencia en los microorganismos susceptibles a desarrollarla y también de resistencia cruzada con otros betalactámicos y carbapenémicos [19].…”
Section: Germen N Amk Cip Gen Etp Sam Fep Atm Nit Sxt Ipm Amp Mer Cazunclassified
“…BLBLIs have previously been compared to carbapenems in systematic reviews with meta‐analyses in patients with bacteraemia with ESBL‐producing Enterobacteriaceae, severe infections, and complicated IAIs, APIs and SSIs . Most have suggested no difference in mortality between groups for both empirical and definitive treatments, proposing BLBLIs as a safe alternative to carbapenems for various severe infections . The effect of definitive treatment with piperacillin/tazobactam vs meropenem in patients with bacteraemia with ceftriaxone‐nonsusceptible Escherichia coli or Klebsiella species (spp.)…”
Section: Introductionmentioning
confidence: 99%